Zn/ZnBr2 Catalysed Reaction of Aldehydes with Allylbromide: Synthesis of 2,6-Disubstituted 4-Bromotetrahydropyrans - Biradar, D. O.; Mane, Y. D.; Sarnikar, Y. P.; Kulkarni, S. G.; Reddy, B. V. Subba; Narsaiah, A. Venkat (SynOpen, 2022)
An efficient approach for the one-pot synthesis of 4-bromotetrahydropyrans in a highly diastereoselective manner via the alkynylation followed by Prins cyclisation is described. The method employs aldehydes and allyl bromide as reactants, with a Zn/ZnBr2 catalytic system in CH2Cl2. A variety of 2,6-disubstituted 4-bromotetrahydropyran derivatives were obtained in good yields.
Keywords: Prins cyclisation; tetrahydropyrans; aldehydes; allylbromides; one-pot reaction